Environmental Management Practices and Sustainable Green Concrete Use in Malaysia's Construction Industry: Challenges, Benefits, and Future Directions - Lim, John; Talukdar, Gaurav (Civil and Sustainable Urban Engineering, 2024)
This review examines the environmental management practices (EMPs) employed within Malaysia's construction sector, with a particular focus on sustainable practices and the adoption of green concrete, including fly ash, rice husk ash, and palm oil fuel ash varieties. The study identifies key challenges, such as low awareness, high costs, weak legal enforcement, and the underdevelopment of green materials in the country. To address these issues, the report proposes solutions such as capacity-building programs, government incentives like tax breaks and grants, regular site inspections, and investment in research and development of green materials. The review also assesses the advantages and limitations of different green concrete types used in Malaysia. The aim of this study is to enhance sustainability efforts and reduce the environmental impact of construction activities through greater awareness, stronger regulatory support, and commitment from all stakeholders. Implementing greener concrete and EMPs is expected to not only mitigate environmental concerns but also yield long-term economic benefits for Malaysia.